Thinking Europe’s “Muslim Question”: On Trojan Horses and the Problematization of Muslims - Bracke, Sarah (Critical research on religion, 2022)
Understanding the ways in which Muslims are turned into “a problem” requires an analytic incorporating the insights gained through the concepts of Islamophobia and anti-Muslim racism into a larger frame. The “Muslim Question” can provide such a frame by attending to the systematic character of this form of racism, explored here through biopolitics. This article develops a conceptualization of Europe’s “Muslim Question” along three lines. First, the “Muslim Question” emerges as an accusation of being an “alien body” to the nation, often expressed through the Trojan horse legend. Second, the “Muslim Question” is elaborated through demands of integration and assimilation, in which the production of difference entangles with calls and measures to regulate Muslims. And third, the “Muslim Question” is brought to life upon the terrain of gender and sexuality, as the imaginary of threat at the heart of the “Muslim Question” is a replacement conspiracy centered on birthrates.